A contrastive analysis between the verb fall" in English and the verb "ngã" in Vietnamese - Nguyễn, Thị Ngân (ĐHNN, 2017)
Language is an important means of communicative and it is also the reflection of human life. Therefore, by contrasting and analyzing languages, we can recognize the similarities and differences not only between the knowledge of the contrasted languages bu (...)